2002
DOI: 10.1093/emboj/21.9.2292
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of cucumber mosaic virus RNA polymerase 2a protein inhibits formation of replicase complex

Abstract: The 2a (polymerase) protein of cucumber mosaic virus (CMV) was shown to be phosphorylated both in vivo and in vitro. In vitro assays using 2a protein mutants and tobacco protein kinases showed that the 2a protein has at least three phosphorylation sites, one of which is located within the N-terminal 126 amino acid region. This region is essential and suf®cient for interaction with the CMV 1a protein. When phosphorylated in vitro, the 2a protein N-terminal region failed to interact with the 1a protein. Since th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
78
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 55 publications
4
78
0
1
Order By: Relevance
“…Othello and not elicit systemic necrosis in the RT4-4 N. benthamiana plants likely reflects the inability of RT4-4 to recognize the 2a protein of this CMV strain. Finally, a role for posttranslational modification in 2a protein recognition, by RT4-4, came from the finding that the CMV 2a phosphorylation mimic mutant failed to elicit the necrosis phenotype (37). Together, these findings are consistent with results of previous studies that identified the 2a protein as the elicitor of a CMV defense response in cowpea (22).…”
Section: Discussionsupporting
confidence: 88%
“…Othello and not elicit systemic necrosis in the RT4-4 N. benthamiana plants likely reflects the inability of RT4-4 to recognize the 2a protein of this CMV strain. Finally, a role for posttranslational modification in 2a protein recognition, by RT4-4, came from the finding that the CMV 2a phosphorylation mimic mutant failed to elicit the necrosis phenotype (37). Together, these findings are consistent with results of previous studies that identified the 2a protein as the elicitor of a CMV defense response in cowpea (22).…”
Section: Discussionsupporting
confidence: 88%
“…This interaction has also been reported for Cucumber mosaic virus (Kim et al, 2002) and Alfalfa mosaic virus (Maurice et al, 2001), the genomes of which consist of three divided RNAs corresponding to RNAs 1, 2 and 3 of the bromoviruses, indicating that the 1a-2a interaction is a common characteristic in the family Bromoviridae. Detectable accumulation of viral RNA was directed by B1S2 and C1S2 combinations.…”
Section: Discussionsupporting
confidence: 71%
“…These phosphatases might contribute to BMV replication by jointly counteracting N-terminal phosphorylation of 2a polymerase, which, for a closely related bromovirus, has been shown to occur in vivo and to inhibit 2a interaction with 1a to promote replication complex assembly (41). Thus, replication complex assembly may be regulated by cell phosphatases as well as kinases.…”
Section: Discussionmentioning
confidence: 99%